PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA MATERI OPERASI HITUNG BILANGAN PECAHAN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION DI KELAS VII SMP NEGERI 4 AMBON - Litaay, Tressya (Jurnal Pendidikan Matematika (JUPITEK), 2019)
Mathematics learning should involve the participation of students so they can be more active and easy to understand the topic they have been studied. Teachers must change the way of teaching and be able to mix interesting and effective learning, so it can encourage students to be active participants in the learning process. One of the choices of cooperative learning models that teachers can apply in the classroom is the Team Assisted Individualization. This research aims to improve the learning outcomes of students in fractional counting operations through cooperative learning models type Team Assisted Individualization in VII Class, SMP Negeri 4 Ambon. The research subjects were 30 students of VII1 grade students on the 2018/2019 school year. This research is a Class Action Research has succeeded to improving student learning outcomes in fractional counting operations in 2 cycles with a percentage of completeness in the first cycle is 41% and the percentage of completeness in the second cycle is 73%.